1994
DOI: 10.1007/bf00227520
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for recovery from a trip in early and late swing during human walking

Abstract: The movement strategies and the underlying organization of the muscular responses for recovery from a tripping perturbation applied in early and late swing during walking were studied in humans. The latencies of the reflex response (60-140 ms) suggested that polysynaptic pathways are involved. The most common movement outcome was an elevating strategy of the swing limb in response to the early swing perturbation and a lowering strategy in response to the late swing perturbation. The elevating strategy comprise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
291
0
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 335 publications
(319 citation statements)
references
References 24 publications
26
291
0
2
Order By: Relevance
“…This is in agreement with the flexor component of the swing limb in response to perturbations in early swing (~ 20% of the swing phase) as described by Eng et al (1994) as part of the so-called 'elevating strategy' .…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…This is in agreement with the flexor component of the swing limb in response to perturbations in early swing (~ 20% of the swing phase) as described by Eng et al (1994) as part of the so-called 'elevating strategy' .…”
Section: Discussionsupporting
confidence: 86%
“…A lengthened swing phase ( -80 ms) was also reported by Dietz et al, (1986) after applying a momentary resistance of 80 ms above the ankle joint at the onset of the swing phase in walking humans. For perturbations in early swing, Eng et al (1994) de scribed a mean swing phase prolongation of 97 mst and they also showed an example of a swing phase which was increased by about 180 ms (their Fig. 5).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations